Positive Surgical Margins in Early Stage Oral Cavity Cancer: An Analysis of 20, 602 Cases. (25th September 2014) - Luryi, Alexander L.; Chen, Michelle M.; Mehra, Saral; Roman, Sanziana A.; Sosa, Julie A.; Judson, Benjamin L.
Abstract : Objective: To report the incidence of positive surgical margins in early oral cavity cancer and identify patient, tumor, and system factors associated with their occurrence. Study Design and Setting: Retrospective analysis of the National Cancer Database. Subjects and Methods: Patients diagnosed with stage I or II oral cavity squamous cell cancer between 1998 and 2011 were identified. Univariate and multivariate analyses of factors associated with positive margins were conducted. Results: In total, 20, 602 patients with early oral cancer were identified. Margin status was reported in 94.8% of cases, and positive margins occurred in 7.5% of those cases. Incidence of positive margins by institution varied from 0% to 43.8%, with median incidence of 7.1%. Positive margins were associated with clinical factors including stage II disease (odds ratio [OR], 1.75; 95% confidence interval [CI], 1.55‐1.98), intermediate grade (OR, 1.20; 95% CI, 1.04‐1.37), high grade (OR, 1.68; 95% CI, 1.39‐2.03), and floor of mouth (OR, 1.78; 95% CI, 1.52‐2.08), buccal mucosa (OR, 2.06; 95% CI, 1.59‐2.68), and retromolar locations (OR, 2.40; 95% CI, 1.85‐3.11). Positive margins were also associated with treatment at nonacademic cancer centers (OR, 1.23; 95% CI, 1.04‐1.44) and institutions with a low oral cancer case volume (OR, 1.45; 95% CI, 1.23‐1.69). Conclusion: Positive margins are associated with tumor factors, including stage, grade, and site, reflecting disease aggressiveness and difficulty of resection. Positive margins also are associated with factors such as treatment facility type, hospital case volume, and geographic region, suggesting potential variation in quality of care. Margin status may be a useful quality measure for early oral cavity cancer.